(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This essay reflects on the culture of gesture present in the relations of scenotechnical work, guiding characteristics of manipulation in the use of work tools and the notions that scenotechnical artists elaborate about the mastery and experience of the craft. We found that it is possible to understand the professional and traditional training that encompasses the making of scenography through the bias of gesture, action, intention and movement, bringing the relationship between the hands and the head closer. To this end, we talked with the concepts of human corporeality (Herold Junior, 2012), translatability (Benjamin, 2008), mirror neurons (Lameira; Gaweyszewski; Pereira Jr., 2006) and rituals (Sennett, 2021).